1987
DOI: 10.1002/lsm.1900070108
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck applications of the milliwatt laser

Abstract: The head and neck surgeon often uses the carbon dioxide laser. With the advent of new instrumentation, the frequency of usage will increase. The CO2 miliwatt laser offers the advantages of tissue welding, as well as cutting and ablation by virtue of the small spot size produced combined with low power output. Potential applications include microvascular and microneural anastomoses. The milliwatt laser can be used endoscopically for tissue resection with a high degree of precision with power densities comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Multiple studies both in vitro and in vivo on the coronal surfaces of teeth have demonstrated that near-infrared (NIR) reflectance imaging yields higher contrast between demineralized and sound tooth structure than visible reflectance and fluorescence. Much of this difference is because the stains do not interfere at wavelengths longer than 1200 nm [5][6][7][8][9][10]. Visible and fluorescence based caries detection systems suffer from false positives resulting from stains on occlusal surfaces [11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…Multiple studies both in vitro and in vivo on the coronal surfaces of teeth have demonstrated that near-infrared (NIR) reflectance imaging yields higher contrast between demineralized and sound tooth structure than visible reflectance and fluorescence. Much of this difference is because the stains do not interfere at wavelengths longer than 1200 nm [5][6][7][8][9][10]. Visible and fluorescence based caries detection systems suffer from false positives resulting from stains on occlusal surfaces [11][12][13][14][15][16].…”
mentioning
confidence: 99%